2016
DOI: 10.1111/liv.13260
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography for the diagnosis of liver fibrosis: a systematic review of economic evaluations

Abstract: Transient elastography is an economically attractive alternative to liver biopsy and other non-invasive diagnostic tests especially for patients with a higher degree of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…TE could be less costly in countries with lower opportunity cost of public funds and in those where nurses perform the exams. Liver fibrosis staging by TE seems to be cost-effective compared to liver biopsy and it was priced from US$ 21 to US$ 73 in the United Kingdom and up to US$ 145 in the United States [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TE could be less costly in countries with lower opportunity cost of public funds and in those where nurses perform the exams. Liver fibrosis staging by TE seems to be cost-effective compared to liver biopsy and it was priced from US$ 21 to US$ 73 in the United Kingdom and up to US$ 145 in the United States [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eradication of hepatitis C virus (HCV) has been associated with lower rates of liver-related complications [ 2 ]. Transient elastography (TE) by FibroScan® (EchoSens, Paris, France) is a validated method to liver fibrosis assessment [ 3 ] and seems to be cost-effective to diagnose cirrhosis compared to liver biopsy [ 4 ]. The high efficacy of direct-acting antiviral drugs (DAAs) has revolutionized the management of patients with CHC.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials showed that FibroScan results, which are expressed in kPa, reported similar results to that of METAVIR score during biopsy interpretation of liver fibrosis in patients with CHC [10]. Moreover, this procedure has also been validated in chronic hepatitis B, NAFLD, alcoholic liver disease, primary biliary cirrhosis, and primary sclerosing cholangitis [14,15]. However, this methodology also has some limitations such as feasibility and unreliability, particularly in obese patients or under the circumstances of limited operator experience [16].…”
Section: Diagnosis Of Liver Fibrosismentioning
confidence: 76%
“…A recent systematic review looking at the cost-effectiveness of FibroScan compared to liver biopsy showed that FibroScan is economically attractive, but does incur added cost of approximately $1250 to $2922[1]. Apart from the cost, the accessibility of FibroScan may be an issue in the primary health care and resource limited setting.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hepatitis C virus (HCV) and hepatitis B virus (HBV) are among the most common causes of liver fibrosis[1]. A determination of the degree of liver fibrosis in these patients is essential to guide management as well as for prognostication[2-6].…”
Section: Introductionmentioning
confidence: 99%